1998
DOI: 10.1074/jbc.273.34.21867
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Inactivates Myosin Light Chain Phosphatase via Rho and Its Target Rho Kinase in Human Endothelial Cells

Abstract: The role of Rho GTPase and its downstream targets Rho kinase and myosin light chain phosphatase in thrombin-induced endothelial cell contraction was investigated. The specific Rho inactivator C3-transferase from Clostridium botulinum as well as microinjection of the isolated Rho-binding domain of Rho kinase or active myosin light chain phosphatase abolished thrombinstimulated endothelial cell contraction. Conversely, microinjection of constitutively active V14Rho, constitutively active catalytic domain of Rho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
296
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(320 citation statements)
references
References 57 publications
15
296
6
Order By: Relevance
“…These effects were reported to be mediated through enhanced myosin phosphatase activity. Essler et al (72) confirmed these observations by showing that agents that elevate cAMP increase myosin phosphatase activity to a similar degree as occurs by direct inhibition of RhoA or suppression of Rho kinase activity with Y27632. BPAE monolayers treated to elevate cAMP then stimulated with thrombin fail to maintain maximal tension development and RLC phosphorylation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These effects were reported to be mediated through enhanced myosin phosphatase activity. Essler et al (72) confirmed these observations by showing that agents that elevate cAMP increase myosin phosphatase activity to a similar degree as occurs by direct inhibition of RhoA or suppression of Rho kinase activity with Y27632. BPAE monolayers treated to elevate cAMP then stimulated with thrombin fail to maintain maximal tension development and RLC phosphorylation.…”
Section: Discussionsupporting
confidence: 68%
“…This increase in myosin phosphatase activity correlates with the decline in basal BPAE RLC phosphorylation and isometric tension, strongly suggesting that the decline in RLC phosphorylation mediates the drop in tension. Studies have shown that agents that interfere with RhoA function block lysophosphatidic acidinduced RLC phosphorylation in fibroblasts (45,71) and prevent thrombin-induced increases in human umbilical vein endothelial cell permeability and RLC phosphorylation (72). These effects were reported to be mediated through enhanced myosin phosphatase activity.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in cytoskeletal reorganization and activation of the RhoA pathway precede these functional responses (6,8,46,47). Hsp90 is also expressed in fibroblasts, platelets, and endothelial cells, and our preliminary experiments 2 suggest a role for Hsp90 in the regulation of PAR-1-mediated morphological changes in these cells.…”
Section: Discussionmentioning
confidence: 89%
“…Inflammatory mediators are known to inactivate myosinassociated phosphatases, which further promoted MLC phosphorylation (111,112). Phosphorylation of MLC phosphatase subunit (MYPT1) was increased by ROS followed by cell contraction (199).…”
Section: B Myosin Light Chain Kinasementioning
confidence: 99%